The regulatory effects of phytosterol esters (PSEs) on gut flora and faecal metabolites in rats with NAFLD. Issue 1 (5th December 2019) - Song, Lihua; li, Yating; Qu, Dan; Ouyang, Pengling; Ding, Xinwen; Wu, PeiYing; Guan, Qi; Yang, Li
Abstract : Nonalcoholic fatty liver disease (NAFLD) can be aggravated by dysregulation of intestinal flora. Phytosterol ester could more effectively regulate the gut flora and related fecal metabolites which were correlated with hepatic steatosis in NAFLD rats. Abstract : Recent studies have shown that the occurrence and progression of nonalcoholic fatty liver disease (NAFLD) can be aggravated by dysregulation of intestinal flora. We previously found that phytosterol esters (PSEs) could effectively prevent the progression of NAFLD. Here, we further investigated the regulatory effect that PSEs have on gut flora and faecal metabolites in rats with NAFLD. Adult SD (Sprague Dawley) rats were randomized into four groups: the normal chow diet (NC), high-fat diet (HFD), low-dose PSE (0.05 g per 100 g BW, PSEL) and high-dose PSE (0.10 g per 100 g BW, PSEH) groups. PSEs were intragastrically administered once a day for 12 consecutive weeks. Our work indicated that high-dose PSE treatment effectively inhibited the increase in liver and abdominal fat indexes ( P < 0.01) and hepatic lipids ( P < 0.01); a high dose PSE treatment effectively corrected the HFD-induced intestinal flora imbalance by changing the diversity. The relative abundances of the four phyla ( Firmicutes, Proteobacteria, Actinobacteria and Verrucomicrobia ) and partial bacteria at the genus level ( Faecalibacterium, Akkermansia, etc .) in the PSEH group were closer to those in the NC group. High-dose PSE intervention significantly increased the relative abundance of Bacteroidetes and Anaerostipes . Compared with the HFD, PSEH treatment significantly decreased the ionic strengths of bile acid metabolism products ( P < 0.05), which were positively correlated with hepatic steatosis. In conclusion, PSE treatment exerts a beneficial effect on NAFLD that is associated with its regulatory action on intestinal flora and faecal metabolites, which might present a new opportunity to develop effective and safe preventive strategies against NAFLD.